CRYPTO Project - What we found so far - Gabriel, Daniela (2022)
ABSTRACT: The presence of non-indigenous species (NIS) is one of the greatest threats to marine biodiversity, presenting potential impacts not only on biodiversity, but also on the economy and public health. When a species is not evidently native or introduced, it is referred to as cryptogenic, an occurrence with consequences for understanding biological invasions. The subregion Azores, with 30% of the EU exclusive economic zone, has 26 species of macroalgae or 6% of its marine flora identified as NIS. This number may increase once the origin of 40 other species that are classified as cryptogenic is clarified. Since many potentially invasive species are currently categorized as cryptogenic, resolving their status is imperative to evaluate their ecological impact and to develop management plans. The CRYPTO Project targets on assessing the origin, distribution and risk of potentially invasive algae, coupled with the application of DNA barcoding, phylogenetic reconstructions, haplotype networks and phylogeographic analyses, coupled with historical assessment and ocean modeling. This project shall contribute to address the EU Horizon 2020’s societal challenge “Climate action, environment, resource efficiency and raw materials”, aiming at the protection of the environment and the conservation of unique Azorean ecosystems. Preliminary results will be presented.